Comparison of the Directorate General of Tax (DGT) Annual Tax Return Reporting Application with the Education Version of the Annual Tax Return Reporting Application - Arniati; Putri, Wika Arsanti; Kurniawan, Dedi; Firmansyah, Erik (Politeknik Negeri Madiun, 2025)
This article compares the e-filing application version of the Directorate General of Taxes with the educational version of the e-filing application made by the Batam State Polytechnic taxation team. The educational version of the e-filing application is an educational application for reporting personal Annual Tax Returns (SPT) based on the web that can be accessed through various devices connected to the internet. The application was compared to determine the effectiveness and material for improving the application as a learning media material. The method used is descriptive qualitative through interviews and trials on the application. The study results indicate that the educational version of the e-filing application is effective and can be used as an educational medium. Still, errors in the application need to be fixed, and features must be added to improve user convenience and fulfil its function as an educational application for reporting annual tax returns.